2021
DOI: 10.1111/gcb.15824
|View full text |Cite
|
Sign up to set email alerts
|

Effects of future climate change on birch abundance and their pollen load

Abstract: Climate change impacts on the structure and function of ecosystems will worsen public health issues like allergic diseases. Birch trees (Betula spp.) are important sources of aeroallergens in Central and Northern Europe. Birches are vulnerable to climate change as these trees are sensitive to increased temperatures and summer droughts. This study aims to examine the effect of climate change on airborne birch pollen concentrations in Central Europe using Bavaria in Southern Germany as a case study. Pollen data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 109 publications
1
15
0
Order By: Relevance
“…Our study shows that in the case of Betula, the importance of DOY on PAP is limited, probably due to less different species in the Betula genus in both Munich and Davos. The main tree species belonging to the genus Betula in the studied area are Betula pendula and Betula pubescens (Rojo et al, 2021), with B. pendula more abundant in this area of Europe (Beck et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Our study shows that in the case of Betula, the importance of DOY on PAP is limited, probably due to less different species in the Betula genus in both Munich and Davos. The main tree species belonging to the genus Betula in the studied area are Betula pendula and Betula pubescens (Rojo et al, 2021), with B. pendula more abundant in this area of Europe (Beck et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…56 The major risk factor for hospitalization in the Melbourne event was allergic rhinitis (87%). 61 Recent studies have shown increased duration of pollen season, peak pollen concentration, total season pollen load, 62 and pollen allergenicity with climate change. 56 A recent study has found that climate change in North America contributes to about 50% of the lengthening pollen season.…”
Section: Ta B L E 2 (Continued)mentioning
confidence: 99%
“…However, these impacts may be modulated by other, species-specific, factors that could offset or even reverse the predicted patterns ( 57 ). For instance, some tree species such as birch ( 58 ) and oak ( 59 ) could suffer the declining of their populations, as they are sensitive to increased temperatures and summer droughts. There have been observation-based studies conducted to explore taxa-specific effects for monitor locations at continental scale ( 21 , 23 ), while mechanistic process-based models used to analyze future pollen patterns for multiple taxa are absent ( 34 ).…”
Section: Discussionmentioning
confidence: 99%